The Moderating Role of Intellectual Capital between Relationship of Bank Specific Factors and Credit Risk of Islamic Banks: Evidence from Pakistan - Muhammad Nawaz; Alias Mat Nor; Habibah Tolos (SEISENSE (PRIVATE) LIMITED, 2019)
Purpose-The Objective of this study is to investigate the moderating role of Intellectual Capital between the relationship of Bank internal factor and Credit Risk in Islamic banks of Pakistan. Design/Methodology-Panel data are obtained from annual reports of 4 Islamic banks of Pakistan from the period 2006 to 2017. These are analyzed using hierarchical regression techniques, via Eviews 9 software. Findings-The results showed that intellectual capital significantly moderates the relationship of bank internal variable and credit risk in Islamic banks in Pakistan. Practical Implications-The study found that Intellectual Capital is a very important driver for credit risk. The investment in Intellectual Capital may lower the credit risk which will further help in the growth and sustainability of the bank and hence the growth in the economy. The results of the study will be useful for bank management, policy maker, and regulator and academia for future research.